Implementation of a Clean and Healthy Lifestyle (PHBS) for Children of Indonesian Migrant Workers (PMI) in Malaysia - Oshin Amirah Rafi; Ahmad Roji Bukoting; Zuhra Azkiana; Siti Nur Azizah; Metha Angelyne Naipospos; Muhammad Ammar Aji; Rafiah Arsyad; Alifiya Fajrin Tafarel; Naba Nabastala; Sabrina Alexandra; Azzahra Fadhlila Aulia Nisa (Journal of Society, Community and Business Development, 2024)
This article focuses on training in implementing a Clean and Healthy Lifestyle (PHBS) for children of Indonesian Migrant Workers (PMI) in Malaysia through washing hands with soap. The aim is to foster a sense of concern among children towards maintaining a clean lifestyle so that children are accustomed to a healthy lifestyle and can apply it to their daily lives. This research involves a structured training program to educate children about the importance of maintaining cleanliness for health and well-being. The main focus is to instill the correct habit of washing hands with soap, considering its proven efficacy in preventing the spread of disease. Implementing PHBS through hand washing training positively impacts the PMI community's general health and welfare in Malaysia. Children know and apply CTPS well and correctly. PMI children can apply CTPS and disseminate it to their families or communities. This health program will cover a wider audience, not only the community of PMI children in Malaysia but also the community of Indonesian citizens in Malaysia.